Optimization of the Use of Volcanic Ash of Mount Sinabung Eruption as the Substitution for Fine Aggregate. (2015) - Karolina, Rahmi; Syahrizal,; Putra, M.Agung; Prasetyo, Tito Agung
Abstract: Mount Sinabung is one of the volcanoes which are categorized as an active volcano in the world. Recently, volcanic activities of some volcanoes in Indonesia are increasing causing the increase in natural materials to be spouted from the volcanoes that can be used as construction materials such as sand, rocks and ash. Chemical substances contained in volcanic ash of Mount Sinabung is more dominated by SiO2 (74.3%), AL2O3 (3.3%), and CaO (1.79) which has been studied in the Research and Industrial Standardization Center, Medan. The content of SiO2 in the volcanic ash was the basis for this research. The objective of this work is to find out the influence of the volcanic ash as the substitution of fine aggregate. The variation of volcanic ash used in the research was 5%, 10%, 15%, 20%, 25%, and 100% with two variations treatment process, by curing the hydrocooling and keeping the room temperature within 28 days. The analysis and the method of the research were referred to SNI 03-0347-1989. Based an experimental results the ideal percentage of variation which had met SNI 03-0347-1989 was identified, that is 10%. Optimum average compressive strength and tensile strength were obtained, 17.19 MPa and 2.67 MPa respectively. Optimum absorbtion were also studied, 4.142%.